Pengaruh ROE dan PBV terhadap Return Saham Sektor Infrastruktur Periode 2018-2024 - Rahmawati, Siti; Juwita, Ratna (Universitas Multi Data Palembang, 2026)
The purpose of this study was to determine the effect of Return on Equity (ROE) and Price to Book Value (PBV) on Stock Returns in Infrastructure Sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2024 period. This study used a quantitative method with a population of 70 companies listed in the Infrastructure Sector for the 2018-2024 period. The research sample consisted of 40 companies selected using a purposive sampling method, with a total sample size of 276. The results showed that, partially and simultaneously, Return on Equity (ROE) and Price to Book Value (PBV) had a positive and significant effect on Stock Returns.